Modeling an ambient agent to support depression relapse prevention - Ab. Aziz, Azizi; Klein, Michel C. A.; Treur, Jan (2009)
One of the challenges for the patients with a history of unipolar depression is to stay healthy throughout their lifetime.In principle, with more prior onset cases, it escalates the risk of the patients to fall into a relapse.In this paper, an ambient agent based model to support patients from relapse is presented. Theories and related works in depression relapse prevention provide a foundation for the formalization of the temporal properties to describe the model.This model was analyzed under several scenarios using simulation and automated verification.